Academic Advisor System (AAS) / Hafizah Ismail - Hafizah, Ismail (2005)
Academic advising is crucial in helping students to excel in their academic field. A good educational plan lays the strong foundation for the positive university experience. Regular meetings with academic advisors will ensure academic success. In attempt to increase the communication effectiveness among students and advisors, the idea of developing an electronic academic advisory system for the Faculty of Computer Science and Information Technology, University of Malaya emerge. The Academic Advisor System (AAS) has tremendous potential to provide students with a support system which is more personal and individual interactions with the academic advisors. This is to ensure and increase efficiency of student's information management for the advisors besides to aid them in keeping track of student's progress. On the other hand, the students will also gain benefits by getting more guides and tips in pursuing excellence. This report will provide a brief description of the Academic Advisor System (AAS). It also includes the functions of the system where it can help the students and lecturers to achieve better communication pattern. The system contains three basic modules that are, Administrator Module, Academic Advisor Module and Student Module. The Academic Advisor System (AAS) is a fully web-based system that features services that allows students to get information from the report, their academic advisors profile as well as the ease of contacting the advisors directly. This is a window based system that can be easily used by the users who are familiar with windows application.